MENGUKUR KESUKSESAN PENGGUNAAN SISTEM INFORMASI ENTERPRISE RESOURCES PLANNING (ERP) TERHADAP KEPUASAN PENGGUNA DAN DAMPAKNYA PADA KINERJA KARYAWAN DI PT UNISEM BATAM - Kiki Rohani; Shinta Wahyu Hati (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2018)
The purpose of this observation is measuring to use Enterprise Resource Plannig information system towards user satisfaction and impact of employee performance in PT UNISEM Batam. The method of data collect using questionnaire method, obeservation method, and documentation method. While for data analysis of using path anaysis method. The results from this observation is level measuring Enterprise Resource Planning (ERP) AIMS and PORTAL by three variable, like as exogen variable (Information System Quality, Information Quality, Service Quality) by intervening variable (User Satisfaction) to see the impaction to endogen variable (Employee Performance).